The new encyclopedia británica in 30 volumes. macropedia VOL. 11 William Benton - Benton, William (Estados Unidos de América: Encyclopedia británica, Inc, 1977)
Chancellor of the exchequer, prime minister, earl history, development of modern lock types, general considerations about locomotion, fossorial locomotion, terrestrial locomotion, arboreal and aerial locomotion, directional control, correct and defective argument forms, the logic of belief, the logic of knowing, the logic of questions, the logic of commands, deonticlogic, temporal logic.
Ilustración, mapa, tabla
Col. Enc
Keywords: 1. ENCICLOPEDIA 2. ENCYCLOPEDIA BRITANNICA -MACROPEDIA VOL. 11 3. REFERENCIA